Syndepositional fractures and architecture of the lastoni di formin carbonate platform: Insights from virtual outcrop models and field studies. (November 2020) - Inama, Riccardo; Menegoni, Niccolò; Perotti, Cesare
Abstract: The recent rapid improvement of Unmanned Aerial Vehicles, together with advances in photogrammetry and Structure from Motion techniques, have enhanced the role of Digital Outcrop Models in many field of geology, due to the possibility to obtain quantitative information from large and inaccessible areas. In this study we integrated Digital Outcrop Modeling techniques and field survey to investigate the architecture of the Middle Triassic platform of Lastoni di Formin . (Italian Dolomites). The research highlighted the presence of two superimposed carbonate bodies. The lower unit (Cassian I) is dominated by low-angle clinoforms dipping north-northeastward and prograding over the basinal San Cassiano Fm. The upper unit (Cassian II) is characterized by a thick sequence of peritidal cycles connected northward to another generation of clinoforms. The inner platform beds of the upper unit display a lateral thickening that is particularly evident near the shelf break, and that has been interpreted as due to the increased subsidence and the consequent down-to-basin tilting of the outermost part of the platform. Moreover, the structural analysis performed on the Digital Outcrop Models and supported by field observations, highlighted the presence of an early generation of faults and joints that indicate an early gravitational deformation of the buildup, possibly caused by the platform progradation and compaction-induced subsidence of the San Cassiano basinal deposits. These WNW-ESE synsedimentary structures are formed by normal faults and extensional joints that are oriented nearly perpendicular to the direction of progradation of the carbonate platform. Highlights: UAV-based Digital Photogrammetry has substantial advantage with respect to ground-based photogrammetry and Laser scanner. Digital Outcrop Modeling allow the analysis and interpretation of structures in a stereo 3D environment, with great resolution and accuracy. The Lastoni di Formin carbonate platform, shows signs of differential subsidence, that affect platform morphology. This deformation is associated with early extensional faults and opening-mode joints that are orthogonal to the direction of progradation.